Integrated Chromatin Accessibility and Transcriptome Landscapes of 5-Fluorouracil-Resistant Colon Cancer Cells - Zhang, Bishu; Lin, Jiewei; Zhang, Jiaqiang; Wang, Xuelong; Deng, Xiaxing (Frontiers in Cell and Developmental Biology, 2022)
Background: 5-Fluorouracil (5-FU) is one of the most effective and widely used chemotherapeutic drugs in the treatment of colon cancer, yet chemoresistance is a common feature of colon cancer treatment, resulting in poor prognosis and short survival. Dynamic reprogramming of chromatin accessibility is crucial for proper regulation of gene transcription associated with cancer drug resistacne by providing the gene regulatory machinery with rapid access to the open genomic DNA. Methods: Here we explored the global chromatin accessibility and transcription changes by the assay for transposase-accessible chromatin using sequencing (ATAC-seq) in combination with transcriptome sequencing of both parental and 5-FU-resistant HCT15 cells, followed by integrative analysis to better understand the regulatory network underlying 5-FU resistance in colon cancer cells. Results: A total of 3175 differentially expressed mRNAs (DEGs), lncRNAs (DELs) and miRNAs (DEMs) related to 5-FU resistance were identified, including significantly up-regulated IL33, H19, miR-17-5p, the down-regulated AKR1B10, LINC01012, miR-125b-5p, and chromatin modifiers such as INO80C, HDAC6 and KDM5A. Construction of ceRNAs regulatory network revealed that H19, HOXA11-AS and NEAT1 might function as ceRNAs associated with 5-FU resistance in HCT15 cells. Moreover, 9868 differentially accessible regions (DARs) were obtained, which were positively (r = 0.58) correlated with their nearest DEGs and DELs. The up-regulated genes related to 4937 hyper-accessible regions were significantly enriched in signaling pathways of MAPK, FOX and WNT, while the 4931 hypo-accessible regions were considered to be involved in declined biosynthesis of amino acids and nucleotide sugars, signaling pathways of Notch, and HIF-1. Analyses of the DAR sequences revealed that, besides AP-1 family, the TF motifs of FOX and KLF family members were highly enriched in hyper- and hypo-accessible regions, respectively. Finally, we obtained several critical TFs and their potential targets associated with DARs and 5-FU resistance, including FOXA1and KLF3. Conclusion: These data provided clear insights and valuable resources for an improved understanding of the non-genetic landscape of 5-FU-resistant colon cancer cells based on chromatin accessibility and transcript levels, which allowed for genome-wide detection of TF-binding sites, potential cis-regulatory elements and therapeutic targets.